TRANCE (Tumor Necrosis Factor [TNF]-related Activation-induced Cytokine), a New TNF Family Member Predominantly Expressed in T cells, Is a Dendritic Cell–specific Survival Factor - Wong, Brian R. (The Rockefeller University Press, 1997)
TRANCE (tumor necrosis factor [TNF]–related activation-induced cytokine) is a new member of the TNF family that is induced upon T cell receptor engagement and activates c-Jun N-terminal kinase (JNK) after interaction with its putative receptor (TRANCE-R). In addition, TRANCE expression is restricted to lymphoid organs and T cells. Here, we show that high levels of TRANCE-R are detected on mature dendritic cells (DCs) but not on freshly isolated B cells, T cells, or macrophages. Signaling by TRANCE-R appears to be dependent on TNF receptor–associated factor 2 (TRAF2), since JNK induction is impaired in cells from transgenic mice overexpressing a dominant negative TRAF2 protein. TRANCE inhibits apoptosis of mouse bone marrow–derived DCs and human monocyte-derived DCs in vitro. The resulting increase in DC survival is accompanied by a proportional increase in DC-mediated T cell proliferation in a mixed leukocyte reaction. TRANCE upregulates Bcl-x(L) expression, suggesting a potential mechanism for enhanced DC survival. TRANCE does not induce the proliferation of or increase the survival of T or B cells. Therefore, TRANCE is a new DC-restricted survival factor that mediates T cell–DC communication and may provide a tool to selectively enhance DC activity.